HUBUNGAN KEBIASAAN SARAPAN, KONSUMSI SUPLEMEN DAN STATUS GIZI DENGAN TINGKAT KEBUGARAN REMAJA LAKI-LAKI USIA 10-17 TAHUN DI SSB TANGERANG SELATAN - Sarah Ulfah Mahaciliawati (2020)
Football is one of the most popular sports in Indonesia. Indonesian Football is ranked 173th out of 210 FIFA member countries as of December 19, 2019 (FIFA, 2019). One of the causes of the low performance of Indonesian football is the low level of fitness of soccer athletes. This study aims to determine the relationship of breakfast habits, supplement consumption and nutritional status with the fitness level of adolescent boys aged 10-17 years at the South Tangerang ASTAM Soccer School. This study used a cross-sectional design with a sample of 50 teenage soccer athletes aged 10-17 years. Data on breakfast habits and supplement consumption were taken using a questionnaire sheet and nutritional status was taken by measuring height and weight, and for the fitness level data was taken using the Balke test method. Relationship analysis was performed using the chi-square test. The results obtained indicate that there is a relationship between breakfast habits (p = 0.023) and nutritional status (p = 0.040) with the level of fitness, but there is no relationship between supplement consumption (p = 0.107)